2019
DOI: 10.1039/c8ta07140c
|View full text |Cite
|
Sign up to set email alerts
|

Readily recyclable, high-performance thermosetting materials based on a lignin-derived spiro diacetal trigger

Abstract: A spiro diacetal structure based on renewable resources was utilized to synthesize thermosets combining ready recyclability and high performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(155 citation statements)
references
References 47 publications
4
150
1
Order By: Relevance
“…For example, Zhang and co-workers prepared a series of vitrimer materials from eugenol, 23 lignin, 24 vanillin, 25 and guaiacol, 25 which were weldable, reprocessable and self-healable. The group of Zhu found that the Schiff base covalent vitrimers prepared from vanillin exhibited the high performance beyond the ones from commercial bisphenol A epoxy resin, [26][27][28] and could be facilely recycled from carbon fiber reinforced composites. 27,28 However, in these reported works tedious chemical modifications on biological resources were necessary to offer reactive sites for curing.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang and co-workers prepared a series of vitrimer materials from eugenol, 23 lignin, 24 vanillin, 25 and guaiacol, 25 which were weldable, reprocessable and self-healable. The group of Zhu found that the Schiff base covalent vitrimers prepared from vanillin exhibited the high performance beyond the ones from commercial bisphenol A epoxy resin, [26][27][28] and could be facilely recycled from carbon fiber reinforced composites. 27,28 However, in these reported works tedious chemical modifications on biological resources were necessary to offer reactive sites for curing.…”
Section: Introductionmentioning
confidence: 99%
“…The sample analysis was executed according to the ASTM D2863/77 standards. The vertical burning tests were conducted in the flame meter, with the dimensions of the sample size being (10 ± 0.002) × (10 ± 0.002) × (0.3 ± 0.002) cm 3 . Each sample was buckled vertically in the center of the column and burned for a period of 3 min.…”
Section: Characterizationmentioning
confidence: 99%
“…The current revolution in polymer technologies reflects the role of thermosetting plastics in their advancement. The dexterous properties of the thermosetting plastics have empowered researchers to widen their possible application in a vast range of fields [1][2][3][4]. The enticing properties such as low viscosity (uncured state), customized modulus (according to application), high thermal stability, smooth process ability and their ability to use with fillers has provided impetus in expanding their commercial applications [5].…”
Section: Introductionmentioning
confidence: 99%
“…These polyacetal vitrimers require no catalyst, show facile monomer recovery and maintain high-T g systems. [231][232][233] Zhu et al were the first to report this acetal motif in a vitrimer network where both transacetalization and acetal metathesis 234 exchange reactions occur to form a permanent dynamic network. This reversible 'click' reaction has potential to easily incorporate many commercial polyols into dynamic networks without the use of catalysts.…”
Section: Permanent Dynamic Network or Vitrimersmentioning
confidence: 99%